Philippe Djian, un artisan du verbe aux marges de la littérature - Bouchoucha, Myriam (Journal of Human Sciences, 2016)
This article tries to present a controversial author : Philippe Djian. Famous but paradoxically unknown, he occupies a special position in contemporary french literature. Literary institution has long considered his works as popular lietrature. His work is classified by criticism as resolutely modern. Relying on American inspiration, it reveals a demanding way of writing, an original universe that suits his time. Djian’s works deserve to raise debate and ask interesting questions : where are the frontiers between literature and popular literature situated? Does literary inspiration have limits ? When a writer becomes an author ?